(3eNJUQ GdHjGf aj fSH Bd YOfGfs - (3LQGH GdOhdI , CMeO Hf eMeO Hf YdhLI GdSLRj GdHZOGOj, CHh GdYHGSs
(3ChdgG (B:s
(3GdMeO ddg GdeaQO ai GdPGJ hGdUaGJ hGdCaYGd hGdQSGdI Gabjg GdefJNH SjO GdYQH hGdYLe ef UahI Bd YOfGf s
(3BNQgG (B:s
(3hjNJe dfG HGdMSfi HLGg fHjfG hPNjQJfG SjOfG hehdGfG eMeO GdMeO ddg QH GdYGdejf hgh MSHfG hfYe Gdhcjd s
(3GNJUQg ef JUGfja GHf NdOhfs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B128s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs